Exact solution of bending problem for continuous sandwich panels with profiled facings - Gosowski, Bronisław; Gosowski, Maciej (Journal of constructional steel research, 2014)
The paper presents a closed-form solution, in the distributional form, of the bending problem for continuous sandwich panels in lightweight cladding that has been derived from the general solution of the system of differential equations for the problem of sandwich beams with thick facings. The analysis covers three-layer members with facings made from profiled metal sheets and a core having good insulating properties, for any number and spacing of elastic intermediate supports. Panels are subjected to bending under uniform transverse load and a load caused by temperature difference. The solution for the multi-span panels inflexibly (rigidly) pin-supported at their ends is derived from the general solution for members arbitrarily supported at their ends. A calculation algorithm for this type of panels is provided. Numerical examples are included to illustrate the influence of the intermediate supports on the effort of both the entire sandwich panel and its profiled facing. Finally, practical concluding remarks are given. •Beam behavior.•Cladding systems.•Composite girders.•Sandwich panels.•Thin walled structures.